Discrete Fourier analysis and wavelets : applications to signal and image processing - Broughton, S. Allen, 1951- (Wiley, 2009)
Most image-processing techniques involve treating the image as a two-dimensional signal and applying standard signal-processing techniques to it. Addressing both the classical and modern mathematical methods of image and signal processing, this book provides the science behind real-world applications.